Unlocking Digital Entrepreneurial Intentions: The Influence of Entrepreneurship Education and Internal Locus of Control in Indonesian Universities - Fitrika Kumala Dewi; Asmar Yulastri; Nizwardi Jalinus; Ganefri; Ernawati; Fadhilah; Elfizon; Fakhrur Rozi; Reni Kurnia (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Several previous studies have shown that entrepreneurship education and internal locus of control have a positive effect on entrepreneurial intentions. However, empirical studies that simultaneously examine these two factors in the context of digital entrepreneurship in Indonesia are still limited. This is important to analyze because Indonesia is among the countries with the highest levels of digital device use worldwide. Therefore, this study aims to analyze the influence of entrepreneurship education, as an external factor, and of internal locus of control, as an internal factor, on students' digital entrepreneurial intentions. This study used an associative quantitative approach, involving 172 students classified as digital natives and Generation Z. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3 and Fuzzy C-Means clustering in JASP. The results showed that entrepreneurship education and internal locus of control had a positive effect on students' digital entrepreneurial intentions. Cluster analysis showed that most respondents were in the moderate group, namely those who had confidence in their personal efforts and entrepreneurial intentions but were still limited in basic entrepreneurial knowledge. These findings imply the need to strengthen entrepreneurship education with an emphasis on developing practical digital entrepreneurship competencies for digital natives.